Empowering People in the Creative Economy Sector to Foster the Dynamic Capabilities of Depok City Government During the Covid-19 Pandemic - Wulandari, Florentina Ratih; Supriyono, Bambang; Muluk, Mujibur RK; Setyowati, Endah (KnE Social Sciences, 2022)
The aim of this research was to examine how people have been empowered in the creative economy sector and the stimulation of the dynamic capabilities of the Depok City Government in developing the creative economy sector. This study used a qualitative approach. The findings revealed that strategies of empowerment efforts shifted due to the Covid-19 pandemic. Thus, operational capacity was reduced. The empowerment of people in Depok City in relation to the development of the creative economy requires collaboration. This study used the theory of dynamic capability formation of Neo and Chen to design a collaborative model for empowering people as part of a penta helix institution. This research can be used to inform dynamic governance development planning for sustainable synergy of people in the creative economy sector. Keywords: operational capability, dynamic capability, penta helix